2008
DOI: 10.1302/0301-620x.90b2.20106
|View full text |Cite
|
Sign up to set email alerts
|

Orthopaedic thromboprophylaxis

Abstract: Thromboprophylaxis remains a controversial subject. A vast amount of epidemiological and trial data about venous thromboembolism has been published over the past 40 years. These data have been distilled and synthesised into guidelines designed to help the practitioner translate this extensive research into 'evidence-based' advice. Guidelines should, in theory, benefit patient care by ensuring that every patient routinely receives the best prophylaxis; without guidelines, it is argued, patients may fail to rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(9 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…In addition, stockings carry a significant cost, particularly in respect of the nursing time associated with excluding contraindications before their application, and with ensuring they are properly applied and remain correctly positioned without complications. 29 30 Further study is necessary to determine the risk–benefit ratio and cost-effectiveness of compression stockings for the contralateral leg following hip fracture.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, stockings carry a significant cost, particularly in respect of the nursing time associated with excluding contraindications before their application, and with ensuring they are properly applied and remain correctly positioned without complications. 29 30 Further study is necessary to determine the risk–benefit ratio and cost-effectiveness of compression stockings for the contralateral leg following hip fracture.…”
Section: Discussionmentioning
confidence: 99%
“…Warwick et al reported various reasons for certain guidelines not being followed in orthopaedic surgery. 21 These included lack of awareness of the guidelines, adverse personal experience with a certain procedure for a specific group of patients, the practicality of implementation and conflicting evidence. The proportions of THR performed in eligible patients have increased since the start of the national hip fracture audit programme, 1 demonstrating that perhaps surgeons are becoming more aware of the guidelines and changing their practice.…”
Section: Discussionmentioning
confidence: 99%
“…No such guidelines exist in Asian countries and where they do exist they are not strictly adhered to27). Coupled with a low incidence are the risks involved with using pharmacological thromboprohylaxis28).…”
Section: Why Do We Need Thromboprophylaxis?mentioning
confidence: 99%
“…Though numerous guidelines exist, there is still lack of adherence27). Even in the US and UK where DVT prevalence is high, guidelines are not fully implemented51,52).…”
Section: Problems With Guidelines and Pharmacological Thromboprophylamentioning
confidence: 99%